A new species of Viguiera (Compositae, Heliantheae) from the state of Queretaro (Mexico) - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2011)
Viguiera paneroana is described as new and illustrated. The species is only known from the Sierra Madre Oriental in the state of Querétaro (Mexico), from an area near the border of San Luis Potosí. According to the information supplied by Drs. José L. Panero and Edward E. Schlling, the DNA sequences indicate that the species is located at the base of the section Maculatae, although it does not belong properly to that section.